PENGEMBANGAN MEDIA INTERAKTIF NORMAPEDIA BERBASIS PROGRAM SATRIA BAIK (SATU HARI TIGA KEBAIKAN) UNTUK MENINGKATKAN TINDAKAN MORAL PESERTA DIDIK DI SMP NEGERI 1 LOCERET - Burhan Nur Asopa; Siti Awaliyah; Sri Untari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research is motivated by obstacles in the implementation of character education at SMP Negeri 1 Loceret, particularly in the aspect of learning media that is less innovative in the era of digital transformation. The focus of this research is to develop Normapedia interactive media integrated with the SATRIA BAIK (One Day Three Goodness) program to strengthen students' moral actions in a real way. Using the Research and Development method with the ADDIE development model, this research goes through the stages of analysis, design, development, implementation, and comprehensive evaluation. The results of the validity test show a very high level of product feasibility reaching 91.87%, covering aspects of material, character, and media design. In the effectiveness test stage on 32 students, a significant increase in moral actions was found with an average score that jumped from 65.12 in the pretest to 84.56 in the posttest. This increase of 19.44 points is supported by an N-gain value of 0.71 which is in the high category and a significance of 0.000. Qualitatively, this program succeeded in increasing discipline consistency by 87% and social empathy by 81%. The main conclusion confirms that the synergy between interactive normative content and digital daily reflection features effectively builds a measurable and sustainable moral habitus. This innovation bridges the gap between students' understanding of ethical theory and their daily behavioral practices in a junior high school environment through the systematic use of technology. This medium supports the creation of a generation of intelligent and high-integrity learners.